Choque hemorrágico experimental em cães anestesiados com isofluorano, tratados com solução hipertônica e colóide associada a diferentes vasopressores - Soares, André Vasconcelos (2010)
The objective was to compare the hemodynamic and metabolic effects of treatment with hypertonic saline and colloid (expanders) associated with different vasoconstrictors in dogs subjected to experimental hemorrhagic shock. Twenty-four healthy adult mongrel dogs were included in the study, with mean body weight of 10.84±3.3kg, males and females. Following anesthetic induction by isoflurane inhalation, the animals were intubated and connected to a partial rebreathing system, and subjected to general inhalational anesthesia with isoflurane using a calibrated vaporizer, which were then maintained at 1MAC (minimum alveolar concentration). Hypovolemia was induced by withdrawal of 5mL kg-1 min-1 of blood from the femoral artery, until the mean arterial pressure reached values between 45 and 50mmHg. After 60 minutes, basal parameters were measured and the treatments were initiated. At this moment, the treatment with colloid and hypertonic solution (4mL kg-1) was carried out. After 10 minutes, the animals were randomly allocated into four groups, according to the continuous infusion to be administered. In GD (dopamine group, n=06), a continuous infusion of dopamine (10μg kg-1 min-1) was administered. The animals in GDB (dobutamine group, n=06) received a continuous infusion of dobutamine (5μg kg-1 min-1) and GV (vasopressin group, n=06) vasopressin at the dose of 0.02IU-1 min-1 by continuous infusion, both diluted in 0.9% NaCl. The GC (n=06), control group, was only treated with the association of hypertonic saline and colloid . The animals were monitored with regards to heart rate, respiratory rate, rectal temperature, systolic, diastolic and mean arterial pressure, central venous pressure, concentration of expired isoflurane, concentration of expired carbon dioxide, fraction of inspired oxygen and arterial blood gas analysis to obtain values of PO2, PCO2, bicarbonate, pH, Na+, K+ and base deficit, hemoglobin and hematocrit. In addition, blood samples were collected to evaluate serum lactate, thromboplastin time, prothrombin time, platelets and complete blood count. The collected data were submitted to variance analysis, where the mean values between groups were analyzed using t-test, and between times within the same group using Tukey test, where the differences were considered statistically significant when p≤0.05. The differences between times within each group were not observed only in the variables of HR in GV and GC, PaO2, K+, MCV, MCHC, total leukocytes (except in GC), segmented neutrophils, monocytes, PT and APTT. The differences between groups were essentially regarding HR (with less proportion of alteration in GV and GC), MAP (GV with higher pressure), PaO2 (lower in GV), K+ (only one time higher in GV) and platelets, in which GC showed the lowest mean value. It can be concluded that the evaluated experimental model is efficient for hemorrhagic shock induction in dogs and requires a blood withdrawal of 42.75±9.2% of the circulating blood volume; the volemia expansion with hypertonic saline and colloid (4mL kg-1) associated or not with dopamine (10μg kg-1 min-1), dobutamine (5μg kg-1 min-1) or vasopressin (0.02IU-1 min-1) is efficient for hemodynamic recovery and metabolic stabilization; and the vasopressin group (GV), though not statistically significant, shows a more favorable clinical tendency in the recovery of hemodynamic and metabolic status in dogs submitted to experimental hemorrhagic shock.